FAKTOR-FAKTOR YANG MEMPENGARUHI TAX AVOIDANCE PADA PERUSAHAAN PERTAMBANGAN DI BEI - Oktavia nur hidayah; endang Masitoh; riana rachmawati dewi (Universitas Prof.Hazairin,SH Bengkulu, 2020)
Tax avoidance is technique used by companies in minimizing the tax burden without violate the rules of taxation legislation. This study aims to examine factor affect tax avoidance. Some independent variabel which used this study include profitability (ROA), leverage (DER), capital intensity, firm size and the proportion of independent commissioners.The population of the research is the company of mining companies listed on Indonesia Stock Exchange. The sample was chosen by purposive sampling which consist of 12 companies in the period of 2016-2018. Data sources is secondary data obtained from BEI website (www.idx.co.id). The analysis technique used in this research is multiple linear regression analysis. Tax avoidance is measured through Effective Tax Rate (ETR). The result of the analysis showed that profitability (ROA) and capital intensity have effect on tax avoidance as for leverage (DER), firm size and the proportion of independent commissioners have no effect on tax avoidance. Therefore, the need for supervision from the government in mailing the reporting regulation of financial statements to minimize the practice of tax avoidance in the company.